2007
DOI: 10.1111/j.1440-1819.2007.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased positive thought disorder with illness duration in patients with schizophrenia

Abstract: It is unclear whether the severity of positive formal thought disorder, a core clinical feature of schizophrenia, is stable or worsening through the chronic course of the illness. The neurocognitive basis for positive thought disorder also remains unclear. The aim of the present paper was to examine the relationship between thought disorder as measured by the Thought Disorder Index (TDI) and duration of illness and neuropsychological indices in 79 patients with schizophrenia.TDI scores increased in proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Thought disorder predicted psychosis transition of young people at-risk mental state (Katsura et al, 2014) and was also found among relatives of patients with schizophrenia (Manschreck et al, 2012). It is moderately stable (trait marker; Wilcox et al, 2012) but becomes exacerbated during the acute episode, tends to increase in severity with illness duration (Maeda et al, 2007), and may also persist during antipsychotic treatment (Remberk et al, 2012). Thought disorder can be as disabling as the other symptoms of schizophrenia, limiting social and occupational functioning (Tirupati et al, 2004) as well as wellbeing and life satisfaction (Sigaudo et al, 2014;Tan et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Thought disorder predicted psychosis transition of young people at-risk mental state (Katsura et al, 2014) and was also found among relatives of patients with schizophrenia (Manschreck et al, 2012). It is moderately stable (trait marker; Wilcox et al, 2012) but becomes exacerbated during the acute episode, tends to increase in severity with illness duration (Maeda et al, 2007), and may also persist during antipsychotic treatment (Remberk et al, 2012). Thought disorder can be as disabling as the other symptoms of schizophrenia, limiting social and occupational functioning (Tirupati et al, 2004) as well as wellbeing and life satisfaction (Sigaudo et al, 2014;Tan et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…For example, the relationships between thought disorder severity and poor general prognosis were found across diagnostic lines Harrow, Silverstein, &Marengo, 1983;Marengo & Harrow, 1987;Racenstein et al, 1999). The other functional relationships, including poorer work functioning and increased psychopathology, were also found regardless of diagnosis Harrow, Silverstein, &Marengo, 1983;Maeda et al, 2007, Marengo & Harrow, 1997Racenstein et al, 1999).…”
Section: Thought Disorder In Schizophreniamentioning
confidence: 93%
“…Specifically, high levels of thought disorder persisting beyond the acute stages of illness have consistently been associated with a particularly negative clinical course and poorer functional prognosis (Andreasen & Grove, 1986;Bowie & Harvey, 2008;Harrow, Silverstein, & Marengo, 1983;Harvey et al, 1990;Marengo & Harrow, 1987;Marengo, Harrow, M., Lanin-Kettering, &Wilson, 1986). Longitudinal studies have reported significant relationships between higher levels of thought disorder at baseline and higher rates of rehospitalization (Harrow, Marengo, & McDonald, 1986;) and duration of illness (Maeda et al, 2007). Research has also suggested a strong positive relationship between thought disorder and delusional severity, across diagnostic lines (Harrow, Silverstein, and Marengo 1983;Harrow, Marengo, & McDonald 1986;Marengo & Harrow, 1997).…”
Section: Thought Disorder In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Thought disorder severity has been shown to increase as a function of illness duration (Maeda et al, 2007;Spohn et al, 1986) as well as number of hospitalizations (Marengo & Harrow, 1997;Spohn et al, 1986). However, inconsistent evidence also exists.…”
Section: Illness Duration Changes In Thought Disorder Have Been Evidmentioning
confidence: 99%